Hubungan antara Homosistein dan Nitrit Oksid pada Hipertensi Esensial di Jawa Tengah, Indonesia - Sunarti Ahmad Husain Asdie, Mohammad Hakimi, Abdul Salam M Sofro (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: The essential hypertension has been related to endothelium-dependent vasodilatation disorders that result of decreasing of nitric oxide (NO) bioavailability. Decreasing of NO can be caused by increase of homocysteine level.Objective: This study is aimed at finding out the effect of homocysteine level on nitric oxide level in essential hypertension, and relationship between NO and blood pressure and hypertension risk in Central Java.Method: This study was case-control nested, in “Surveillance of Non-Communicable Diseases” in Purworejo, Central Java. The subjects were men with essential hypertension and 20-60 years old that had normal value of urine creatinine, blood glucose, cholesterol and triacylglycerol. They didn’t take antihypertension drugs. The methods of Pfeiffer, et al. was used to identify total plasma homocysteine level. NO level was determined by Nitric Oxide Colorimetric Assay Kit (BioVision Cat.K262200).Result: The homocysteine level of the hypertension is higher than that of the non- hypertension (16.15 + 12.69 vs 12.73 + 5.73; P=0.035), whereas the nitric oxide level of the hypertension is lower than that of the non-hypertension (8.22 + 1.88 vs 9.49 + 3.05; P=0.003). Homcysteine level was significantly correlated with nitric oxide level (P=0,016). Negative correlation between nitric oxide level and systolic and diastolic pressures was significant (P=0,005; P=0,045), respectively in subjects of 40-60 years old but not significant (P=0,106; P=0,269), respectively in those younger (20-39 years old). The relationship between nitric oxide and hypertension risk was significant (P=0,005) in subjects of 40-60 years old but not significant (P=0,062) in those younger (20-39years old).Conclusion: The high homocysteine level is a risk factor of hypertension, that reduces the NO bioavailability. The reducing of NO bioavailability was related to increase of blood pressure and hypertension risk, especially it was in the old men.Keywords: homocysteine, nitric oxide, hypertension, Central Java, Indonesia